THE RESEARCH AND EXPERIMENT OF A LINEAR ELECTRICAL GENERATOR FROM SEA WAVE ENERGY - Anh, Nguyen Dong; Hai, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2017)
This paper presents some results of research and experiment of a linear electrical generator from sea wave energy. On the basis of the results of analysis, dynamic calculation and simulation of the operation the device works in the vertical direction of sea waves and is fixed on the sea floor, the buoy of device floats on the surface of sea and transfers the energy of sea waves to the electrical generator. The output power of the device is operated stably at 200 W during experiment at the sea, the output voltage is at 220 VAC with frequency of 50 Hz and is a pure sine wave. These results show that the device is completely reasonable with conditions in Vietnam’s sea.